Protein Cryoprotective Activity of a Cytosolic Small Heat Shock Protein That Accumulates Constitutively in Chestnut Stems and Is Up-Regulated by Low and High Temperatures - Maria-Angeles Lopez-Matas; Paulina Nuñez; Alvaro Soto; Allona, Isabel; Casado, Rosa; Collada, Carmen; Maria-Angeles Guevara; Aragoncillo, Cipriano; Gomez, Luis (Plant physiology (Bethesda), 2004)
Heat shock, and other stresses that cause protein misfolding and aggregation, trigger the accumulation of heat shock proteins (HSPs) in virtually all organisms. Among the HSPs of higher plants, those belonging to the small HSP (sHSP) family remain the least characterized in functional terms. We analyzed the occurrence of sHSPs in vegetative organs of Castanea sativa (sweet chestnut), a temperate woody species that exhibits remarkable freezing tolerance. A constitutive sHSP subject to seasonal periodic changes of abundance was immunodetected in stems. This protein was identified by matrix-assisted laser-desorption ionization time of flight mass spectrometry and internal peptide sequencing as CsHSP17.5, a cytosolic class I sHSP previously described in cotyledons. Expression of the corresponding gene in stems was confirmed through cDNA cloning and reverse transcription-PCR. Stem protein and mRNA profiles indicated that CsHSP17.5 is significantly up-regulated in spring and fall, reaching maximal levels in late summer and, especially, in winter. In addition, cold exposure was found to quickly activate shsp gene expression in both stems and roots of chestnut seedlings kept in growth chambers. Our main finding is that purified CsHSP17.5 is very effective in protecting the cold-labile enzyme lactate dehydrogenase from freeze-induced inactivation (on a molar basis, CsHSP17.5 is about 400 times more effective as cryoprotectant than hen egg-white lysozyme). Consistent with these observations, repeated freezing/thawing did not affect appreciably the chaperone activity of diluted CsHSP17.5 nor its ability to form dodecameric complexes in vitro. Taken together, these results substantiate the hypothesis that sHSPs can play relevant roles in the acquisition of freezing tolerance.